Vivencias de las personas adultas mayores de la parroquia rural San Pedro deVilcabamba cantón Loja, frente al abandono familiar, año 2023. - Gaona Álvarez, Leidi Viviana (2023)
Older adults are considered a vulnerable group in society and in many cases, due to their physical, economic, psychological and emotional conditions, they are victims of denigrating acts, including family abandonment, subjecting them to exclusion processes; these situations directly affect their quality of life. The main objective of this research study was to analyze the experiences of older adults of the rural parish "San Pedro de Vilcabamba", Loja canton, in the face of family abandonment, year 2023. The methodology used corresponds to the qualitative paradigm and the phenomenological approach, which allowed having a broader vision of the context. The study population consisted of 241 elderly people, 91 of whom showed traits of family abandonment. It should also be noted that the data collection was carried out through three focus groups 3 differentiated by age ranges, whose characteristics were situations of abandonment by their family (children). The results indicate that the older adults do not hold feelings of resentment or resentment towards their relatives for the situations of abandonment they go through, on the contrary, they normalize it and look for excuses to understand and justify their actions, they also state that it is their decision to remain in their place of birth until the last day of their lives, even if this means being alone, which causes them nostalgia and anguish. In each of their expressions they hang on to their religious beliefs, however, there is a need for physical, psychological and social attention.